The effect of a non-circular chainring on cycling performance - Horvais, N.; Samozino, P.; Hintzy, F. (The Engineering of Sport 6, Volume 1 Developments for Sports, 2006)
The aim of this work was to analyse the effect of a non-circular chainring during sub and supra-maximal cycling conditions on physiological, mechanical and muscular data. Results showed that the use of the non-circular chainring was beneficial during top and bottom dead centres by decreasing the effective force for a same external force for sub-maximal condition and by increasing the crank angular velocity for supra-maximal condition. However, this non-circular chainring was without effect during the pedal downstroke.